2017
DOI: 10.12816/0039064
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI CSF Flowmetry in Evaluation of Hydrocephalus in Pediatric Patients

Abstract: Background: phase contrast MR imaging is a rapid, simple and non-invasive technique which is sensitive to even small CSF flows, and can be used to evaluate CSF flow both qualitatively and quantitatively. Cine phase contrast MR images show CSF flow in a dynamic, more easily appreciable, and in a more pleasing manner, allowing the delineation of obstruction, if present, along the portions of CSF pathway where obstruction is common (foramen of Monro, acqueduct of Sylvius) Patients and Methods: the study includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In agreement with researchers (1) , among causes of hydrocephalus, aqueduct stenosis(AS) is the commonest that could be idiopathic or secondary to inflammatory pathologies, In different studies , it was found that 14 out of 25 patients (4) and 9 out of 20 patients (1) were AS while in this present study it was 11 out of 20 patients have AS.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with researchers (1) , among causes of hydrocephalus, aqueduct stenosis(AS) is the commonest that could be idiopathic or secondary to inflammatory pathologies, In different studies , it was found that 14 out of 25 patients (4) and 9 out of 20 patients (1) were AS while in this present study it was 11 out of 20 patients have AS.…”
Section: Discussionsupporting
confidence: 92%
“…is was evidenced by the reduced aqueductal flow on cine MR images and consistent with the studies by Lucic et al, Parkkola et al, and Abdelhameed et al, wherein reduced aqueductal flow was observed in patients with hydrocephalus as a result of aqueductal stenosis. [19][20][21] is further affirms the role of PCMRI in the differentiation of communicating and non-communicating hydrocephalus.…”
Section: Discussionmentioning
confidence: 56%